2001
DOI: 10.1021/cm001408y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Metal Oxides Synthesized by the Nanoscale Casting Process Using Supercritical Fluids

Abstract: Nanoporous metal oxides (TiO 2 , Al 2 O 3 ) have been synthesized using activated carbon templates with supercritical fluid solvents by using the nanoscale casting (NC) process. The precursors were dissolved in supercritical CO 2 and attached to activated carbon fibers or powders as templates. After removal of the activated carbon templates by calcination in air at 873 K or by treatment in oxygen plasma, the nanoporous TiO 2 or Al 2 O 3 replicating the macroscopic shapes of the activated carbon templates was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 11 publications
0
44
0
Order By: Relevance
“…The setup for scCO 2 deposition is similar to those reported in literature [21]. For the synthesis of mesoporous Co 3 O 4 , 5 mL of a certain concentration of Co(NO 3 ) 2 ethanol solution was put in a stainless steel autoclave (with a volume of 40 mL), while 0.5 g of SBA-15 powder was placed in a filter-paper bag which was fixed in the upper part of the autoclave so that the template was not in contact with the precursor solution.…”
Section: Synthesis Of Mesoporous Co 3 Omentioning
confidence: 90%
See 1 more Smart Citation
“…The setup for scCO 2 deposition is similar to those reported in literature [21]. For the synthesis of mesoporous Co 3 O 4 , 5 mL of a certain concentration of Co(NO 3 ) 2 ethanol solution was put in a stainless steel autoclave (with a volume of 40 mL), while 0.5 g of SBA-15 powder was placed in a filter-paper bag which was fixed in the upper part of the autoclave so that the template was not in contact with the precursor solution.…”
Section: Synthesis Of Mesoporous Co 3 Omentioning
confidence: 90%
“…The low viscosity, zero surface tension, high diffusivity, as well as good dissolving capability of scCO 2 make it an ideal medium to carry the target compounds into 1D long channels of the mesoporous silica [20,21]. In the present work, we use scCO 2 as the solvent and ethanol as a co-solvent to carry Co(NO 3 ) 2 into the channels of SBA-15 (hereafter the process is called as scCO 2 deposition).…”
Section: Introductionmentioning
confidence: 99%
“…[87±92] In this technique, low molecular weight precursors such as tetraethyl orthosilicate (TEOS), [87,90] platinum acetylacetonate [Pt(acac) 2 ], [88] titanium isopropoxide [Ti(OiPr) 4 ], [91,92] and aluminium acetylacetonate [Al(acac) 3 ] [91] were dissolved in scCO 2 and contacted with porous template materials such as activated carbon [87±92] and palm nutshell. [89] After treatment in the SCF, the samples were recovered and the template material was removed by calcination or oxygen plasma treatment.…”
Section: Nanoscale Castingmentioning
confidence: 99%
“…[89] After treatment in the SCF, the samples were recovered and the template material was removed by calcination or oxygen plasma treatment. Using this method, it was possible to produce templated nanoporous platinum, [88,89] silica, [87,89,90] titania, [89,91,92] and alumina materials. [91] In the case of silica, it was shown that the samples prepared using solutions of TEOS in scCO 2 had much higher surface areas (900±1400 m 2 g ±1 )…”
Section: Nanoscale Castingmentioning
confidence: 99%
See 1 more Smart Citation